On Maximal Semi Continuous Functions in Topological Spaces - M. Ittanagi, Basavaraj; P. Siddapur, G. (International Journal of Engineering and Technology, 2018)
Study of functions called maximal semi continuous, strongly maximal semi continuous, maximal semi irresolute, maximal semi s-continuous and super maximal semi continuous functions are introduce and investigate. During this process, some of their properties are obtained.Â Â